Program Pembiayaan Mitraguna Berkah Bank Syariah Indonesia Kcp Mulyosari Terhadap Guru Inpassing MI dan MTs - Fauzatul Laily Nisa; Rehan Isnan Purwandika; Utami, Anisa Fitria (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Teacher Inpassing is the process of equalizing positions, ranks, and classes for teachers who are not civil servants (PNS) to have positions, ranks, and classes comparable to civil servant teachers. Non-civil servant teachers who are eligible to apply for inpassing are teachers who already have an Educator Certificate. Inpassing teachers have a disadvantage, namely that the salary they get is not every month, especially private MI and MTS teachers, this makes their economy disrupted. Bank Syariah Indonesia provides a solution with the existence of a special blessing mitraguna financing for inpasing teachers with financing that can be done every 3 (three) or 4 (four) months. The purpose of this study is to determine the role of mitraguna blessing financing in improving the economy of inpassing teachers. This research uses Qualitative method with descriptive approach. Based on the results of the research, Mitraguna Blessing financing has considerable potential to build the economy of inpassing teachers.